2017
DOI: 10.1080/01635581.2018.1406123
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic Modified Sweet Potato Pectin Induces Apoptosis like Cell Death in Colon Cancer (HT-29) Cell Line

Abstract: Sonication led up to seven-fold decrease in molecular weight. The degree of methoxylation (DM) decreased more than two-fold. Moreover, the galacturonic acid (GalA) content increased up to 92%, arabinose and galactose content increased. The SSPP inhibited cell proliferation with the IC values 0.5 mg/ml and 0.75 mg/ml for 400 W and 200 W SSPP, respectively. Moreover, 14.41 ± 1.64% cell cytotoxicity was elicited by 400 W SSPP and 6.83 ± 0.80% by 200 W SSPP. Both SSPPs induced apoptosis with 400 W SSPP eliciting 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…Strong increases of apoptotic cell population, as well as sub-G 1 cellular fraction, suggested that PC augmented proapoptotic and cytostatic properties of this anticancer drug. Proapoptotic activity of pectins have been already demonstrated for many types of pectin preparations in a variety of experimental settings, e.g., in ovarian cancer (SolC [36]), prostate cancer (fractionated pectin powder [38], SolC [39]) as well as in colon cancer (pectic oligosaccharides [40], sweet potato [41], ginger [31], and beetroot pectin [33]). Modified citrus pectin was recorded to increase caspase-3 activity and to modify the cell cycle of ovarian cancer cells in a similar way as observed for apple pectin PC in the present work [36].…”
Section: Discussionmentioning
confidence: 99%
“…Strong increases of apoptotic cell population, as well as sub-G 1 cellular fraction, suggested that PC augmented proapoptotic and cytostatic properties of this anticancer drug. Proapoptotic activity of pectins have been already demonstrated for many types of pectin preparations in a variety of experimental settings, e.g., in ovarian cancer (SolC [36]), prostate cancer (fractionated pectin powder [38], SolC [39]) as well as in colon cancer (pectic oligosaccharides [40], sweet potato [41], ginger [31], and beetroot pectin [33]). Modified citrus pectin was recorded to increase caspase-3 activity and to modify the cell cycle of ovarian cancer cells in a similar way as observed for apple pectin PC in the present work [36].…”
Section: Discussionmentioning
confidence: 99%
“…Pectin is the source of POS in natural products and mainly exists in citrus peel [it mainly consists of a homopolymer of 1–34-linked os- d -galactosyluronic acid with 85.7% methylated esterification and a rhamnogalacturonan I (RG-I) fragment] ( 38 ), sugar beet pulp (a high degree of acetylation and a relatively high neutral sugar content) ( 39 ), potato pulp (it has highly branched RG-I domain) ( 21 , 40 ), and additional sources, etc. Pectin consists of fundamental units of α (1–4)-galacturonic acid, which is often acetylated and/or methylated.…”
Section: Pos Preparationmentioning
confidence: 99%
“…Pectin oligosaccharides can stimulate apoptosis process in human colonic adenocarcinoma cells, show protective functions for cardiovascular tissues, reduce the damage caused by metals, and have anti-obesity effects, antitoxic, antibacterial, and antioxidant activities ( 20 ). Sweet potato pectin possesses anticancer activity and induces the apoptosis of CC cells and may be a cancer therapeutic drug ( 21 ). The pectin derivative with maleoyl groups also shows antitumor properties for CC ( 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…The cytotoxicity studies of pectin-naringenin conjugate showed anti-cancer activity against NIH: OVCAR-5 cells 21 . Ogutu et al, observed the apoptosis effect of Ultrasonic Modified Sweet Potato Pectin in Colon Cancer (HT-29) Cell Line 22 . The above studies describe the cytotoxic activity of pectin, which could exploit to identify active compounds against human hepatoma cancer cells for further studies.…”
Section: Resultsmentioning
confidence: 99%